Short Communication: Global warming - Problem with environmental and economical impacts - SHIVANI M. RAI (Smujo International, 2013)
Abstract. Rai SM. 2013. Short Communication: Global warming – Problem with environmental and economical impacts. Nusantara Bioscience 5: 102-105. The present article is focused on global warming, which is an important global problem being faced by the humankind. The article discusses about the causes of the global warming, such as green house gases. The earth receives energy from the Sun in the form of solar radiations with small amount of infra red and ultraviolet rays. A part of these radiations is absorbed by green house gases which results into warming of the earth. These radiations increase temperature on the universe and are one of the most important global problems. The efforts from all the countries of the world are required for reduction of emissions of green house gases.